Endophytic fungi from Amomum siamense - Bussaban B. (2014)
Endophytic fungi were isolated from apparently healthy organs of the wild ginger Amomum siamense Criab., including leaves, pseudostems, and rhizomes, collected from two sites in Doi Suthep-Pui National Park, Thailand. Endophytes were relatively common with an isolate prevalence of 70%-83% at the two sites sampled in the wet and dry seasons. The endophyte assemblages from the two sites were diverse and comprised 7 Ascomycetes and 26 mitosporic fungi. Colletotrichum "gloeosporioides" (Penz.) Penz. & Sacc. in Penz., Glomerella spp., xylariaceous fungi, and Phomopsis spp. were consistently dominant as endophytes on Amomum siamense, but many rare species and mycelia sterilia were also recorded. There was no significant difference between the number of isolates recovered from leaves containing vein tissues and those containing intervein tissues, independent of leaf age. Most taxa showed a preference for either leaf tissue or pseudostems. Two new Ascomycetes species, Gaeumannomyces amomi and Leiosphaerella amomi, were discovered from leaves and rhizomes, respectively, and four species of Pyricularia, including three new species, were isolated from leaves.